Competência legislativa em matéria de processo e procedimento - Dall Olio, Gustavo (2010)
The scientific evolution of Procedure Law had an impulse from the conceptual elaboration of the phenomenon process and procedure. With the advent of Federal Constitution in 1988, that granted legislative competence on process and procedure for the Union, to the States and to the Federal District (privatively and concurrently), came the necessity of the formulation of objective and specific criterion that allows the empiric separation of different kinds of normative acts, delimitating, therefore, the field of political entities. This study, that examines the evolution of the Federation in Brazil, issue imbricated to the division of power subject, has as a scope to formulate a proposal that helps the interpreter in the solution of conflicts on process and procedure, where vague, fluid and inaccurate concepts are multiplied (general and special rules)